Palladium-catalyzed post-Ugi arylative dearomatization/Michael addition cascade towards plicamine analogues. Issue 44 (3rd November 2021) - Liu, Chao; Zhao, Ruiqi; Song, Liangliang; Li, Zhenghua; Tian, Guilong; He, Yi; Van Meervelt, Luc; Peshkov, Vsevolod A.; Van der Eycken, Erik V.
Abstract : The combination of Ugi-4CR and palladium-catalyzed dearomatization sets the stage for the straightforward construction of plicamine derivatives in a rapid, highly efficient and step-economical manner. Abstract : A palladium-catalyzed intramolecular cyclization of Ugi-adducts via a cascade dearomatization/aza-Michael addition process has been developed. Diverse plicamine analogues are constructed in a rapid, highly efficient and step-economical manner, through the combination of an Ugi-4CR and a palladium-catalyzed dearomatization. The synthetic utility of this approach is illustrated by further functional group transformations.